Implementasi Pendekatan TaRL dengan Model PBL Pada Peserta Didik Kelas IIA SDN Sendangguwo 01 - Nahdia Ahya Putri Ahya; Siti Patonah; Khafidlotur Rofiqoh; Kartinah (Jurnal Lensa Pendas, 2024)
Researcher found a lack of students activity during the learning process which was carried out by forming heterogeneous groups. Based on these problems, researchers conducted a research by applying the Teaching at the Right Level (TaRL) approach with the Problem Based Learning (PBL) model to grade IIA students at Sendangguwo 01 elementary schooll and aimed to explore students' learning using the TaRL approach with the PBL model in grade IIA at Sendangguwo 01 elementary school. The research method used is a descriptive qualitative approach. The research participants were 29 studentes in grade IIA at Sendangguwo 01 elementary school that consisted of 14 men and 15 women. The research results showed that students have a positive perception of learning using the TaRL approach with the PBL model. They consider this learning can provide an opportunity to work together with classmates, learn to solve the problems, and they can be in a group with equal abilities. This research provides a deeper understanding of students’ perceptions with TaRL approach learning with the PBL learning model in class IIA at Sendangguwo 01elementary school.